Членистоногі-шкідники зерна колосових культур при зберіганні та заходи щодо регулювання їх чисельності в Лівобережному Лісостепу України - Бондаренко, Ілона Володимирівна (НУБіП України, 2016)
Дисертація на здобуття наукового ступеня кандидата сільськогосподарських наук за спеціальністю 16.00.10 – ентомологія. – Національний університет біоресурсів і природокористування України, Київ, 2016. Досліджено ентомоакарокомплекс зерна колосових культур у період зберігання, виялено 81 вид членистоногих, які належать до 31 родини, 7 рядів та трьох класів. Встановлено домінуючий комплекс шкідників. Вивчено залежність їх розвитку від абіотичних чинників, визначено ступені сумарної щільності зараженості (забрудненості) досліджуваних партій зерна, відповідність їх максимально допустимим рівням. Проведено оцінювання стійкості наявних сортів пшениці озимої щодо основних видів шкідливих комах. Оцінено ефективність сучасних інсектицидів, мікробіологічного препарату Бітоксибациліну, обґрунтовано їх раціональне використання в системі хімічного захисту зерна. Визначено економічну ефективність хімічного захисту зерна пшениці озимої в період зберігання від основних шкідників.
The dissertation for obtaining degree of candidate of agricultural sciences by specialty 16.00.10 – entomology. – National University of Life and Environmental Sciences of Ukraine, Kyiv, 2016. In conditions of Forest-steppe zone of left-bank of Ukraine species composition of arthropod-pests of grain stocks of spiked cultures was thoroughly studied. 81 species of pest were found, which belong to 31 families, 7 orders, which are found with different freguency in stocks of grain. Coleoptera and Psocoptera – 35.2 and 32.2 % respectively were characterized with the highest species diversity. The complex of the dominant economically meaningful insects was specified, which includes: fodder mite (Glycyphagus destructor Ouds.); hunting mite (Cheyletus eruditus Schrk.); dust mite (Zercoseius ometes Ouds.); book louse (Troctes divinatorius Mull.); grain weevil (Sitophilus granarius L.); rice weevil (Sitophilus oryzae L.); red flour beetle (Tribolium castaneum Herbst.); short-horned beetle (Cryptolestes ferrugineus Steph.); sawtoothed grain beetle (Oryzaephilus surinamensis L.); corn sap beetle (Carpophilus dimidiatus F.); lesser grain borer (Rhyzopertha dominica F.); indian meal moth (Plodia interpunctella Hbn.); cacao moth (Ephestia elutella Hb.). The dependence of development of the dominant species of pest from abiotic factors such as temperature, moisture and fodder base was studied. The duration of formation of generations of major species of pest under different temperature conditions and nutrition compositions (wheat and barley grains) was determined. At higher temperatures (30 °С) the development of generation of insects was 5–8 days shorter in comparison with 23 °С. The high sensitivity to choice of food for sawtoothed grain beetle was noted. The contamination from first to fourth degrees of grain batches and the contamination from first to fifth degrees of stocks of spiked cultures were detected. The varieties of modern winter wheat were tested on the ability to resist to grain weevil and rice weevil, lesser grain borer, sawtoothed grain beetle, red flour beetle. The resistance of wheat variety is represented by types of antiksenoz (unpleasantness) and antibiosis (inhibition of development). The varieties of Ukrainka poltavska and Liutenka showed integrated resistance to this species of insects. The technical efficiency of insecticides Aktellik (16.0 ml/t) and K-Obiol (42.0 and 84.0 ml/t) was 100 % against adults of lesser grain borer, grain weevil, rice weevil, sawtoothed grain beetle, red flour beetle and confused flour beetle on fourteenth day of observations. The use of insecticides mixtures with Bitoksibatsillin showed high results in comparison with individual chemical preparations. Aktellik with BTB ensured the technical efficiency at level 90.3 % in application rate of 8.0 ml/t + 3.0 l/t and K-Obiol (21.0 ml/t + 6.0 l/t) – 100 % on the thirtieth day of accounting. Microbiopreparation of Bitoksibatsillin (3.0 and 6.0 l/t) has also shown high efficiency between 80.0 to 100 % (depending on application rate). The protective effect of Aktellik and K-Obiol against grain weevil, rice weevil, sawtoothed grain beetle and red flour beetle was preserved for four months at level 100 %. Aktellik provided high efficiency regarding lesser grain borer during one month. In further accounts the toxicity of preparation decreased to 72.2 % after 120 days of researches. The economic efficiency of insecticides and their mixtures against dominant species was determined. The highest level of profitability was 304.6 % in variant with use of K-Obiol (21.0 ml/t). The indicators of economic efficiency at use of mixtures of insecticides in half of the norm were slightly lower, but this contributes reduction of pesticide load on stocks of grain.
Keywords: зерно; зерносховище; елеватор; шкідники; ентомоакарокомплекс; зараженість; забрудненість; стійкість сортів; інсектицид; мікробіологічний препарат; ефективність; grain; warehouse; elevator; pests; entomoacarocomplex; infestation; contamination; resistance of variety